Estudio del perfil de la demanda turística del cantón Pujilí provincia de Cotopaxi, año 2021 - Analuisa Puco, Fatima Elizabeth (2021)
The purpose of this research project was to contribute with important information about the tourism demand in order to reactivate the tourism in Pujilí canton of Cotopaxi province and Ecuador. For the fulfillment of the methodology, a descriptive study was designed using the deductive method and with a quantitative approach, using the survey technique, for which a table of systematization of variables was elaborated, classifying them into four categories: demographic, socioeconomic, motivation and preferences, Once approved, it was proceeded to validate the collecting information tool which was the questionnaire applied to 385 hikers who have been visited several spots in Pujilí, according to the manual of inventories of attractions and generation of tourist spaces, therefore, once the data was collected, the respective tabulation was made through descriptive and inferential statistics. Concluding that, the highest percentage of visitors who travels to the canton is 97% who are of Ecuadorian nationality and 3% of foreign nationality, subsequently, In the gender it was possible to see a high percentage of men (53%) who would take the initiative to travel and 74% of women, the people who visit the canton are mainly from Pichincha province with a percentage of 34% are travelers who drive and increase the economic income in the canton, in addition, the results of their daily expenses were obtained, the 86% spend between 1 to 100 dollars, thus their visit lasts less time and finally, it was possible to estimate the profile of the tourist demand of the canton.